Concepts Of Satisfaction with Family And Family Life - Aymatova Dilorom Ruzimurotovna (Zien Journals, 2024)
A family is a small group based on marriage or childbirth. Its members are intertwined with the unity, mutual assistance and spiritual responsibility of the monk. In the family, it is necessary that its members feel positive on their own, regardless of age and gender,as well as realize for themselves,, as a comfort zone’. It is only then that satisfaction with family life can be achieved. This article reflects on the same issue
Keywords: family; comfort zone; social function; development